Aransemen “Saya Mau Ikut Yesus” pada Permainan Ansambel Quarted Band dalam Ibadah di Gereja GPdI Agave Bangun - Yefta Sihombing; Boho P. Pardede; Aprinaldi Simorangkir; Monang Asi Sianturi; Roy Josep Hutagalung (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
The scientific paper with the title arranging the song I want to follow Jesus in the quarted band ensemble playing in the GPdI Agave Bangun Service is research that discusses how to apply the branch of arrangement, namely reharmonization, to the composition I want to follow Jesus. This research uses qualitative research methods using observation, interviews and documentation. Arrangement comes from the Dutch word Arrangement, which means adjusting a musical composition to the number of singers' voices or musical instruments based on an existing composition so that the essence of the music does not change. The arrangements influence the formation of the rhythm and harmony produced by the quarted band ensemble at GPdI Agave Bangun. The results of the research show that the problem of this research is that the drum and bass, which are the main components in the quarted band ensemble, are out of sync between the two instruments which will affect the quality of the arrangement. The piano is often melodic but can also be an accompaniment instrument, the piano playing pattern becomes a rhythmic fulcrum that will change the character and dynamics of the song. Reharmonization of the piano chords is the main reason the writer arranged the song I want to follow Jesus by changing the character of the song from sad to straightforward. Substitution chord theory, voicing and slash chord techniques are the main ingredients for researchers in composing. The type of research used in this research is qualitative research, with the data collection techniques used are observation, interviews and documentation. The final result of this research is as reference material for church musicians to increase their repertoire of playing variations to accompany worship in the church.